Indicators of lime reactivity in soil: particle size, carbon dioxide evolution, and citric acid titration. Issue 6 (12th May 2022) - Heinrich, Aaron; Sullivan, Dan; Moore, Amber D.
ABSTRACT: Accurate predictions of the short-term reactivity of liming products are needed for situations where rapid soil pH adjustment is desired. Lime efficiency (LE) describes the capacity of a liming material to neutralize soil acidity in comparison with a finely ground CaCO3 standard (LE = 100%). Our objectives were to evaluate LE for calcitic liming materials varying in particle size at 1–12 months after soil incorporation using pH change (LEpH ) and CO2 evolution (LECO2 ) as response indicators, and to evaluate a 15-min citric acid (CA) test as a predictor of LE. We evaluated LE for lime particle size separates from 10 to 200 USA mesh (< 2000 µm to 75 µm) and for three commercial liming products (65, 25 and 11 µm average particle size) in a sandy loam soil. In field microplots, it took 6 months to achieve LE of > 80% with lime particles of <60 mesh (< 250 µm). LEpH was linearly related to LECO2 at one month following lime incorporation into soil. Both LEpH and LECO2 increased as a function of CA test values, as described by logarithmic equations. Lime particle size, CO2 evolution, and CA test values were all useful indicators of short-term LE.